ANALYSIS OF SEGMENTAL AND SUPRA-SEGMENTAL ERRORS OF JAVANESE ENGLISH SPEAKERS IN PP. DARUL ULUM AL-FADHALI - Althaf Afida (Language-Edu, 2021)
In the concept of second language acquisition, first language is able to influence second language skill. As international language, English is also become foreign language of Javanese speakers. This study analyze the errors of Javanese when pronouncing English text both is segmental (consonants and vowels) and supra- segmental (length, tone, intonation and stress) aspects. There are five participants who read the English text “The Greedy Lion”. They have to be born in Java, speak Javanese since they are child, and have Javanese language surroundings. The result shows that: 1) In pronouncing consonants, they made errors in /v/, /θ/, /ð/, /s/, /z/, /r/, /k/, and /g/; 2) In pronouncing vowels, they made errors in /i/, /ɪ/, /u/, /ʊ/, /e/, /ə/, /ʌ/, /ɔ/, /æ/, and /a/; 3) in supra-segmental aspect, they made errors in stressing word, intonating sentence, and lengthening diphthong.